Anti-nociceptive and anti-inflammatory effects of hydroalcoholic extract and essential oil of Pinus eldarica in animal models - Valiollah Hajhashemi; Behzad Zolfaghari; Pooya Amin (Mashhad University of Medical Sciences, 2021)
Objective: Several species of Pinus have shown anti-nociceptive and anti-inflammatory properties. This study was aimed to evaluate anti-nociceptive and anti-inflammatory effects of hydroalcoholic extract of bark and essential oil of leaves of P. eldarica in animal models.  Materials and Methods: Hydroalcoholic extract of bark and essential oil of leaves of P. eldarica were prepared and phenolic content and essential oil composition were analyzed using Folin-Ciocalteu method and GC/MS, respectively. Anti-nociceptive effect was assessed using acetic acid, formalin and hot plate tests in male Swiss mice (25-30 g) and for evaluation of anti-inflammatory activity, carrageenan test in male Wistar rats (180-200 g) and croton oil-induced ear edema in male mice, were used. Involvement of opioid, α2-adrenergic, 5-HT3 receptors and adenosine triphosphate (ATP)-dependent K+ channels in pain relief was tested using naloxone, ondansetron, yohimbine and glibenclamide. Results: The total phenolic content of the extract in terms of gallic acid equivalent was 404.9±7.7 mg/g of the extract powder. P. eldarica hydroalcoholic extract (200 and 400 mg/kg) and essential oil (100 and 200 µl/kg) significantly (all, p <0.001) decreased pain behavior in acetic acid and formalin tests but not in hot plate test. The extract and essential oil suppressed edema in carrageenan and croton tests. Glibenclamide partially reversed the anti-nociceptive effect of hydroalcoholic extract while the other antagonists were ineffective. Conclusion: Hydroalcoholic extract of bark and essential oil of leaves of P. eldarica significantly decreased acute and chronic pain as well as inflammation. ATP-dependent K+ channels mediate a part of the observed anti-nociceptive effect.